2021
DOI: 10.3389/fsufs.2021.701870
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Diversity Dynamics in Acid Mine Drainage and Acid Mine Drainage-Polluted Soils: Implication on Mining Water Irrigation Agricultural Sustainability

Abstract: Environmental degradation related to mining-generated acid mine drainage (AMD) is a major global concern, contaminating surface and groundwater sources, including agricultural land. In the last two decades, many developing countries are expanding agricultural productivity in mine-impacted soils to meet food demand for their rapidly growing population. Further, the practice of AMD water (treated or untreated) irrigated agriculture is on the increase, particularly in water-stressed nations around the world. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 145 publications
2
8
0
Order By: Relevance
“…These findings are further supported by Raletsana et al [ 37 ], who noted 46% reduced potato yield with AMD water irrigation, while Choudhry et al [ 38 ] reported a 62% decrease rice yield in rice due to elevated acidity, EC, Fe, Mn, SO 4 2− , and diminished availability of P, K, and Zn in AMD-contaminated paddy field. Hence, the phytotoxic effects of AMD acidity and the contamination of agricultural soil and crops, and potential transfer of toxic HM into the food chain, underscore concerns over untreated AMD water agriculture [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are further supported by Raletsana et al [ 37 ], who noted 46% reduced potato yield with AMD water irrigation, while Choudhry et al [ 38 ] reported a 62% decrease rice yield in rice due to elevated acidity, EC, Fe, Mn, SO 4 2− , and diminished availability of P, K, and Zn in AMD-contaminated paddy field. Hence, the phytotoxic effects of AMD acidity and the contamination of agricultural soil and crops, and potential transfer of toxic HM into the food chain, underscore concerns over untreated AMD water agriculture [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Witwatersrand Basin in South Africa, with a long history of gold mining, is one of the regions affected by AMD, discharging about 202 million L/day AMD wastewater [ 4 ], This water resource has been suggested as an important potential solution to the region's freshwater shortage [ 4 , 5 ], but poses a threat to ecological systems, agricultural land, and human health due to its high acidity and nonbiodegradable heavy metals (HM) contamination. Therefore, it must be treated to a quality suitable for use in irrigated agriculture and non-potable applications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On one hand, the minerals are usually accompanied by various potentially toxic trace metals (PTEs) such as Pb, Cd, Cr, Mn, Ni, Cu, Tl, and Zn (Liu et al, 2019). On the other hand, the high acidity increases the bioavailability of PTEs and can affect microbial activity, community structure, and nutrient production (Baek et al, 2021;Munyai et al, 2021). For example, toxic metals including Cd, Cr, and Pb, and excessive amounts of metals Cu, Mn, Ni, and Zn, retard the growth of vegetables and have chronic effects on humans including kidney damage, cardiovascular failure, anaemia, and cancer (Edelstein and Ben-Hur, 2018).…”
Section: Introductionmentioning
confidence: 99%